1999
DOI: 10.1080/10473289.1999.10463913
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Decay Rates in Residences

Abstract: In urban and suburban settings, indoor ozone exposures can represent a significant fraction of an individual's total exposure. The decay rate, one of the factors determining indoor ozone concentrations, is inadequately understood in residences. Decay rates were calculated by introducing outdoor air containing 80-160 parts per billion ozone into 43 residences and monitoring the reduction in indoor concentration as a function of time. The mean decay rate measured in the living rooms of 43 Southern California hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 1 publication
9
71
0
Order By: Relevance
“…No fan power or pressure measurements were reported. Walker et al (2009) and Walker and Sherman (2012) modeled ozone penetration for typical building leaks based on laboratory and field estimates of model parameters and found that ozone levels indoors were a few percent higher for supply compared to exhaust mechanical ventilation and that overall penetration rates were in the 5 to 10% range -consistent with field data measured in other studies: Stephens et al (2011), Lee et al (1999 and and Stock et al (1985). Opening windows essentially bypasses the envelope filtration with indoor deposition being the only removal mechanism and the ozone concentrations in Walker et al (2009) and Walker and Sherman (2012) rose to almost 50% indoors -again consistent with measured field data (see the bibliography in Walker et al (2009).…”
Section: Envelope Filtrationmentioning
confidence: 50%
“…No fan power or pressure measurements were reported. Walker et al (2009) and Walker and Sherman (2012) modeled ozone penetration for typical building leaks based on laboratory and field estimates of model parameters and found that ozone levels indoors were a few percent higher for supply compared to exhaust mechanical ventilation and that overall penetration rates were in the 5 to 10% range -consistent with field data measured in other studies: Stephens et al (2011), Lee et al (1999 and and Stock et al (1985). Opening windows essentially bypasses the envelope filtration with indoor deposition being the only removal mechanism and the ozone concentrations in Walker et al (2009) and Walker and Sherman (2012) rose to almost 50% indoors -again consistent with measured field data (see the bibliography in Walker et al (2009).…”
Section: Envelope Filtrationmentioning
confidence: 50%
“…In typical homes and offices they calculate deposition velocities between 0.025 and 0.062 cm/s. Lee et al (1999) report an average deposition velocity of 0.049∫0.017 cm/s in 43 Southern California homes. Morrison (1999) has developed a general model of reactive gas deposition to indoor surfaces.…”
Section: Removal By Indoor Surfacesmentioning
confidence: 97%
“…The values range from 1.4 h ª1 in a stainless steel chamber to 7.6 h ª1 in a highly ventilated device fabrication cleanroom. Lee et al (1999) have measured ozone removal rates in 43 Southern California homes -the most extensive set of measurements in the literature. They report a mean surface removal rate constant of 2.80∫1.30 h ª1 .…”
Section: Removal By Indoor Surfacesmentioning
confidence: 99%
“…O 3 concentrations in southern California homes are considerably lower in air-conditioned buildings (Lee et al 1999). We previously reported results of an O 3 exposure assessment study in Alpine that showed only small correlations between 12-hr daytime personal passive measurements of O 3 (median: spring 1994, 15.5 ppb; fall 1994, 12.7 ppb) and centralsite O 3 (median: spring 1994, 54 ppb; fall 1994, 60 ppb).…”
mentioning
confidence: 99%